Hasil Belajar Matematika Melalui Model PJBL dalam Blended Learning Ditinjau dari Tingkat Integritas Akademik - Dresthya Aranggani; Erlina Prihatnani (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Integrity is honest, fair behavior and shows consistency between words and actions. In the field of education, the term academic integrity is known. Academic integrity is behavior that is in accordance with the norms of truth in the academic context. there are five aspects in academic integrity, namely honesty, trust, fairness, respect, and responsibility. Academic integrity is very important to have so that a person behaves ethically in the learning process. a decrease in academic integrity has the potential to affect students' professional lives when working later. Lack of integrity in academics in a person can be influenced by several factors, both internal and external. The internal factor causing the lack of integrity is academic anxiety. This happens because of the worries that arise over failure in the exam, so students do various ways to get good test scores. the purpose of this study is to determine with the application of the PjBL learning model, whether there are significant differences in learning outcomes between students with high, medium and low integrity. The project given in the application of the PjBL model is expected to provide a different, fun, meaningful and challenging learning experience for students. The method used in this research is through cluster random sampling technique. The application of PjBL in blended learning with a project-shaped evaluation model produces the same learning outcomes for the three integrity groups. With the highest average learning outcomes coming from the medium integrity group followed by the high integrity group and the lowest average coming from the low integrity group.